Characterizing the effects of controlled temperature and relative humidity on liquid water transport behavior of cotton/lycra elastic woven fabric - Yong Wang; Qifan Qiao; Jiqiang Cao; Chao Zhi; Changlong Li; Yuan Tao (Materials Research Express, 2021)
Liquid transport (wicking) has great effect on the physiological comfort, since it directly determines the moisture management of fibrous assemblies. For elastic fabric structures, the wickability primarily depends on several factors, such as tensile strain and ambient conditions (e.g., temperature, relative humidity). The main purpose of this work was to systematically clarify the effects of water temperature and relative humidity on vertical liquid water transport of as-prepared cotton/lycra elastic woven fabric experimentally and theoretically. On the experimental side, the results indicated that our as-prepared fabric exhibited a water temperature-strengthening effect, while a humidity-weakening effect was produced simultaneously. In other words, a higher water temperature results in a higher equilibrium wicking height, whereas a higher relative humidity results in a decreased wicking height. Furthermore, the underlying wicking mechanism in each case was graphically unraveled. On the analytical side, the proposed Laughlin-Davies model turns out to be appropriate, it can replicate the wicking characteristics of fabric in both of these cases qualitatively and quantitatively. These findings are expected to provide a deep understanding of fabric wicking under a realistic regime.